Juvenile polyposis of infancy in a child with deletion of BMPR1A and PTEN genes: Surgical approach - Oliveira, PH (2013)
Juvenile polyposis of infancy is the most severe and life-threatening form of juvenile polyposis. This disease typically presents in the first two years of life with gastrointestinal bleeding, diarrhea, inanition, and exudative enteropathy. In very few reports concerning this entity, a large deletion in the long arm of chromosome 10 (10q23), encompassing the PTEN and BMPR1A genes, was found. The authors report a case of delayed diagnosis of juvenile polyposis of infancy at 6years of age. A 3.34Mb long de novo deletion was identified at 10q23.1q23.31, encompassing the PTEN and BMPR1A genes. The disease course was severe with diarrhea, abdominal pain, inanition, refractory anemia, rectal bleeding, hypoalbuminemia, and exudative enteropathy. A sub-total colectomy, combined with intraoperative endoscopic removal of ileal and rectal stump polyps, was required for palliative disease control.